Prototype Pendeteksi Kebakaran Hutan Berbasis Internet - Guswan, Gizan; Rahmadya, Budi (CHIPSET, 2024)
Astimesadvance,forestsareincreasinglythreatenedanddamaged,oneofwhichisforest fires.Forestfiresoccurduetotwofactors:naturalfactorsandhumanfactors.Naturalfactorscausingforest fires include climate change and rising temperatures. Another factor is human activitythat damages forests for purposes such as industrial interests and land expansion. Currently,forest fires have been designated as a national natural disaster by the government because theyhave caused significant losses across various sectors. Forest fire management is generallyconducted through firefighting and post-fire handling, alongside prevention campaigns aimedat discouraging forest burning among communities. Early warning systems and detection arecrucialforforestfireprevention. Thetechnicalaspectissupportedbygovernmentinfrastructuresuch as observation towers to monitor fire-prone areas. Forest or peatland fires can start fromsmall ignition points and escalate into large blazes. During Indonesia's dry seasons, numerousignitionpointstypicallyoccurinKalimantanandSumatra,fueledbydrygrass,wood,andotherflammable materials. To identify fire-prone areas, the Keetch-Byram Drought Index method iscommonly used. This method assesses fire hazard based on dryness levels in specific regions.Accurate analysis helps prevent and manage land fires effectively. Regular education andoutreachprogramsareessentialtoraiseawarenessamongthepublicaboutthedangersofforestfires,preventionmethods,andproperfiremanagement.Theseeffortsaimtoincreasecommunity involvement in forest conservation. Furthermore, education serves as a means todemonstratepracticalfirefightingtechniquesandstrategiesdirectlyinthefield."